Perancangan Sistem Pengendalian Manajemen yang Terintegrasi pada PT. Hok Seng Jayaperkasa untuk Meningkatkan Efisiensi Operasional - Itan, Iskandar; Jennifer, Jennifer (Journal Of Human And Education (JAHE), 2024)
Hok Seng Jayaperkasa is facing several significant challenges in management control that affect the company’s performance and operational efficiency. To address these issues, the Community Service (PkM) activity is focused on designing a Microsoft Access-based management control system. This initiative aims to enhance inter-departmental coordination, oversight, risk assessment, and inventory management. The methods used include direct observation, interviews with employees and management, and literature review to obtain a comprehensive understanding of the existing problems. The results of this activity show that the implementation of the new management control system can improve workflow, reduce operational costs, and increase overall productivity. Additionally, this system supports compliance with industry regulations and enhances decision-making quality by providing accurate and timely information. With effective implementation, it is expected that the system will make a significant contribution to the growth and sustainability of PT. Hok Seng Jayaperkasa and improve the company’s performance in the long term.